Effect of skipping breakfast on cerebral blood flow and cardiovascular function under a mental load in healthy female students - Sawai, Asuka; Nie, Naoyo; Sawai, Shinya; Tsuzuki, Kayoko; Tochikubo, Osamu (Progress in Nutrition, 2020)
This study aimed to investigate the influence of skipping breakfast on the performance of a mental arithmetic load from the physiological viewpoint. In 16 healthy female university students who habitually eat breakfast, cerebral blood flow measured (CBF) by near-infrared spectroscopy, blood glucose, ketone bodies, autonomic nerve activity measured by electrocardiography, and energy expenditure measured by indirect calorimetry were monitored during a mental arithmetic load after eating and not eating breakfast, and cross-over evaluations were performed. The number of correct answers given to the arithmetic test; the levels of blood glucose, energy expenditure, and respiratory quotient; and the changes in deoxyhemoglobin in the CBF were significantly lower on the day breakfast was eaten than not eaten (p